A COMPARATIVE STUDY OF THE RELATIONSHIP BETWEEN TIKTOK USE AND SOCIAL ANXIETY AMONG FEMALE STUDENTS AT SMAN 9 MAKASSAR AND SMA IT AR-RAHMAH MAKASSAR - M. Fais Satrianegara; Nildawati; BS Titi Haerana; Berlian (Universitas Airlangga, 2025)
Introduction: Adolescent social anxiety, particularly among females, is reported at 28.2% versus 25.4% among males. Globally, it affects about 7% of the population annually and contributes to higher risks of non-communicable and mental disorders. Social media, especially TikTok, is suspected to play a crucial role in this issue. Aims: This study compared the relationship between TikTok use intensity and social anxiety among female students from two educational settings: SMAN 9 Makassar (public) and SMA IT Ar-Rahmah (Islamic-based private). Methods: A quantitative cross-sectional design was used with 86 respondents selected through multistage and total sampling. Instruments included the Social Anxiety Scale for Adolescents (SAS-A), four questionnaires on social media use, and Welltory for physiological data. Results: Social anxiety was reported by 55.8% and 46.4% of SMAN 9 Makassar and SMA IT Ar-Rahmah students, respectively. The Mann-Whitney U test showed no significant difference between schools (p=0.163). The Chi-Square test revealed a significant relationship between TikTok use intensity and social anxiety (p=0.000). Duration of use also differed significantly (p=0.019), with SMAN 9 and SMA IT Ar-Rahmah students averaging 112.7 and 73.8 minutes/day. TikTok content type was significantly related to social anxiety at SMAN 9 Makassar (p=0.000) but not at SMA IT Ar-Rahmah (p=0.960). User activity and general social media intensity showed no significant link. Conclusion: Social anxiety levels did not differ significantly between schools, but TikTok use intensity and content type were strongly associated. Multilevel interventions involving screening, digital literacy, and policy collaboration are recommended.